Efektivitas Pemanfaatan Aset Daerah Bidang Pertanian di Kabupaten Indragiri Hulu - Meli Andari; Zulkarnaini Zulkarnaini (Jurnal Ilmiah Wahana Pendidikan, 2022)
Effectiveness is a measure of how far the success of an organization in achieving its goals. Utilization of assets that can be done is by borrowing. The Department of Agriculture and Fisheries of Indragiri Hulu Regency is currently providing loans in the form of agricultural equipment assistance, namely borrowing excavators. The purpose of this loan is to help farmer groups who have difficulty in cultivating their land which in the process requires the assistance of a heavy excavator. Then, the purpose of this study is to look at the effectiveness of the utilization of regional assets in the agricultural sector in Indragiri Hulu Regency and identify factors that influence the implementation of the excavator loan. This type of research is a qualitative method with data collection techniques with interviews, observations, and documentation. The results of this study have not gone well because there are still some indicators that are not yet effective, namely indicators on time. Then, for the inhibiting factors in its implementation, namely administration that has not been managed properly and human resources that have not been optimal.